Are green bonds delivering on their green promise? : A qualitative study exploring the motives and effects of green bond issuances - Rouhelo, Kiia (My University, 2022)
There is a global concern over combatting climate change and the need for rapid actions. Debt capital markets, with the largest pool of capital globally, also play a critical role. Green bonds have been introduced as one potential solution and the market has grown rapidly in recent years after the first one was issued in 2008. A distinct feature of green bonds is that the bond proceeds are to be ring-fenced for green projects. The green bond market has evolved through self-regulated market standards and now voluntary EU standard is also under development. The green bond market is characterized by high investor demand and more restricted supply, leading to often observed pricing difference compared to conventional bonds, the so-called green premium. Despite the noble aims of the instrument, it has faced criticism and concerns. For instance, the additionality of the instrument, whether green bonds are raising capital for green projects that would not otherwise happen, has been questioned. However, it has been suggested that the greatest impact of green bonds could come from the new standards of practice and cultural change that they are catalyzing. Thus, the objective of the thesis is to examine the potential green bonds possess in facilitating the financing for the sustainability transition. The aim is approached by exploring the motivations and barriers for engaging in the green bond market. In addition, the study intends to understand how green bonds affect the operations of different market participants and influence market practices. For this purpose, different green bond market participants, including issuers, investors and underwriting banks, are approached. The research is designed as a case study, using Finland as the context. The data is collected through nine (9) semi-structured interviews, which are analyzed using theory-directed content analysis as a method. The study yielded several interesting findings. Firstly, in terms of delivering impact, the biggest benefit of green bonds may be the increased transparency and awareness these instruments are creating in the financial markets. Secondly, green bond issuers are mainly motivated by the ability to connect their organizational level sustainability work to financing and communicate that to different stakeholders. External pressures and market expectations are also increasingly driving green bond issuance. Thirdly, the lack of internal expertise and capabilities or lack of eligible projects are usually the main barriers to green bond issuance. Lastly, the additionality of green bonds cannot be claimed, at least in a way it is typically understood, as green bonds are not financing projects that would not have received financing otherwise. As the green bond market and green definitions have evolved in recent years and will continue to evolve, more data on the environmental impacts of green bonds becomes available, which may provide fruitful avenues for future research.
Keywords: green bonds, green finance, sustainable finance